Minimum mortality temperature by cause of death and age group: A multi-country observational study (1990–2019) - Seunghyun Eom; Aurelio Tobias; Masahiro Hashizume; Daewon Yang; Claire Demoury; Eric Lavigne; Aleš Urban; Klea Katsouyanni; Francesco Sera; Paul Lester Carlos Chua; Susana das Neves Pereira da Silva; Dominic Royé; et al. (Environmental Research, 2026)

Ammonia capture from wastewater via electrochemical pH control using conductive membrane: Toward a circular nitrogen economy - Vincent Po Hong Lee; Jiawei Sun; Wing Chi Au; Xiaolu Li; Xinxin Wei; Shao Lu; Jason Chun-Ho Lam; Alicia Kyoungjin An (Desalination, 2026)

Thermally buffered remnant melts sustain explosivity after caldera collapse: Cryptotephra evidence from Aira, Japan - Xuan-Yu Chen; Yi-Gang Xu; Xiao-Long Huang; Ji-Hoon Kim; Shuang Yan; Peng-Li He; Myong-Ho Park; Jong-Hwa Chun (Earth and Planetary Science Letters, 2026)

Hexamermis jengi n. sp. (Nematoda: Mermithidae) parasitizing grasshoppers and the invasive fall armyworm in Taiwan and Thailand - Ping-Chieh Lee; Ace Kevin S. Amarga; Wen-Hua Chen; Li-Hsin Wu; Chuan-Kai Ho; Chun-I Chiu; Ming-Chung Chiu (Journal of Invertebrate Pathology, 2026)

Wind tunnel study of wind flow over low- to high-rise building arrays using PIV and POD analysis - Yunming Zhang; Ziwei Mo; Fei Li; Ruiqi Wang; Guoliang Chen; Shiyun Liu; Yixun Liu; Chun-Ho Liu (Building and Environment, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Substrate-driven microbial diversity and functional potential of plastisphere biofilms in a dynamic coastal ecosystem of northeastern Taiwan - Priyanka Muthu; Sakcham Bairoliya; Gowri Krishna Girija; Li-Chun Tseng; Bin Cao; Jiang-Shiou Hwang; Ying-Ning Ho (Environmental Pollution, 2026)

Mapping drag coefficient using CFD and machine learning with application to urban canopy model - Jie Chen; Ziwei Mo; Congyu Li; Wai-Chi Cheng; Chun-Ho Liu (Sustainable Cities and Society, 2025)

Research note: assessing human preferences for natural landscapes—an analysis of ChatGPT-4 and LLaVA models - Yu-Hsin Tung; Zhe-Rui Yang; Meng-Wei Shen; Chun-Yen Chang; Chien-Chung Chen; Li-Chih Ho (Landscape and Urban Planning, 2025)

Co3O4 confined in activated carbon-supported Mg/Al-LDH for µM peroxymonosulfate activation with minute-level antibiotics degradation - Tao Li; Weikun Sun; Jian Zhang; Shengqin Liu; Hongbin Chen; Zumin Qiu; Jason Chun-Ho Lam (Chemical Engineering Journal, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

ZnAl alloy and organosulfur hybrid energy storage for long term cyclability - Qing Liu; Zhiyong Zheng; Chun Huang; Gun Jang; Qingyun Dou; Yong Li; Shengyang Huang; Baohuai Zhao; Yongan Wu; Yi Zhang; Bo-Kyong Kim; Xu Yu; et al. (Chemical Engineering Journal, 2025)

Ultrasensitive, fast and flexible piezoresistive strain sensor based on Te nanomesh - Yiyang Wei; Changyong Lan; Yu Luo; Fangjia Li; You Meng; SenPo Yip; Chun Li; Yi Yin; Johnny C. Ho (Chemical Engineering Journal, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

DNA barcode reference database and gap analysis for biomonitoring Hong Kong’s marine animals - Mei-Hong Zhao; Jack Chi-Ho Ip; Chun Ming How; Yi-Xuan Li; Dumas Deconinck; Jian-Wen Qiu (Regional Studies in Marine Science, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Turbulence scale and strength analysis in the roughness and inertial sublayers over urban areas: A wind tunnel study - Fei Li; Ruiqi Wang; Guoliang Chen; Ziwei Mo; Naoki Ikegaya; Chun-Ho Liu (Building and Environment, 2025)

Microbiome flexibility enhances the resilience of the potentially invasive coral Tubastraea aurea to abrupt environmental changes: Insights from a shallow water hydrothermal vent transplantation study - Gowri Krishna Girija; Li-Chun Tseng; Priyanka Muthu; Yu-Ling Chen; Ying-Ning Ho; Jiang-Shiou Hwang (Science of The Total Environment, 2024)

Roles of direct and indirect photodegradation in the photochemical fates of three 3rd generation fluoroquinolones - Yitao Li; Jason Chun Ho Lam; Yuhe He; Yuefei Ruan; Xinming Huang; Theodora Nah (Journal of Hazardous Materials, 2024)

Application of Cytochrome P450 Monooxygenases in Plant for Rapid Detection of 2,3,7,8 Tetrachlorodibenzodioxin in the Contaminated Sites - Ho Man Leung; Ka Chun Sung; Lai Yan Woo; Wing Yin Mo; Kwai Chung Cheung; Chi Kin Au; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Assessment of Spatial Variability of Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Soils and Fungal Disease Status of Trees Grown in Hong Kong Areas - Ka Chun Sung; Ho Man Leung; Chi Fung Lee; Tohidi Fatemeh; Wing Yin Mo; Lai Yan Woo; Kwai Chung Cheung; Uchenna Ogbonnaya; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Wildfire-vegetation-climate-human interactions in the central Taiwan region during 17.3–2.0 cal kyr BP, inferred from sediments of Toushe Basin - Abdur Rahman; Yuan-Pin Chang; Hong-Chun Li; Ling-Ho Chung; Yu-Min Chou; Liang-Chi Wang (Quaternary Science Reviews, 2024)

Solar-driven adaptive radiative cooling coating with polymer carbon dots-enhanced photoluminescence for urban skin - Quan Gong; Ho Chun Wong; Jianheng Chen; Pei Li; Lin Lu (Chemical Engineering Journal, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

A new method for detecting urban morphology effects on urban-scale air temperature and building energy consumption under mesoscale meteorological conditions - Ruiqing Du; Chun-Ho Liu; Xian-Xiang Li (Urban Climate, 2024)

Turbulent transport mechanism in the roughness sublayers over idealized urban areas and its implication to street-level ventilation - Ruiqi Wang; Chun-Ho Liu; Fei Li; Ziwei Mo (Sustainable Cities and Society, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Interaction among local flows, UHI, coastal winds, and complex terrain: Effect on urban-scale temperature and building energy consumption during heatwaves - Ruiqing Du; Chun-Ho Liu; Xianxiang Li; Chuan-Yao Lin (Energy and Buildings, 2024)

Correlations among high-order statistics and low-occurrence wind speeds within a simplified urban canopy based on particle image velocimetry datasets - Fei Li; Chiyoko Hirose; Wei Wang; Chun-Ho Liu; Naoki Ikegaya (Building and Environment, 2024)

Electrical stimulation induces anti-tumor immunomodulation via a flexible microneedle-array-integrated interdigital electrode - Yixuan Pan; Yangxi Zhang; Xueying Shi; Dongdong Li; Xiaodan Xu; Bing Xiao; Ying Piao; Jiajia Xiang; Shiqun Shao; Frederic Chun-Yip Ho; Youqing Shen; A. Ping Zhang; et al. (Science Bulletin, 2023)

The NOx-O3 photochemical reactive air pollutant dispersion around an isolated building—the role of turbulence model and building aspect ratio - Yunfei Fu; Xisheng Lin; Lu Li; Mengyuan Chu; Chun-Ho Liu; Zengshun Chen; Cruz Y. Li; K.T. Tse (Building and Environment, 2023)

Microbiome variability in invasive coral (Tubastraea aurea) in response to diverse environmental stressors - Gowri Krishna Girija; Li-Chun Tseng; Yu-Ling Chen; Pei-Jie Meng; Jiang-Shiou Hwang; Ying-Ning Ho (Frontiers in Marine Science, 2023)
The Indo-Pacific native azooxanthellate Tubastraea (Scleractinia) has been identified as an invasive marine species with substantial environmental, economic, and social implications worldwide. Despite their exceptional invasive capacity, our understanding of the role of their symbiotic microbiota in host resilience, as well as their response to ambient environmental conditions, remains limited. In this study, we analyzed the symbiotic bacterial communities found in the tissue and mucus of Tubastraea aurea from different habitats along the northeastern coast of Taiwan. These habitats included two extreme sites (a hydrothermal vent [HV] and a copper mining [CM] site) and two normal environments (inlet of a nuclear power plant [NPP] and a habitat adjacent to a conservation zone [CZ]). We employed full-length 16S rRNA sequencing (~1.5 kilobases) to determine coral-associated microbiome responses to local environments. Results showed significant variations in bacterial communities between corals from extreme and normal habitats. Chemoheterotrophic Endozoicomonas bacteria dominated the tissue samples from the HV and CM sites, whereas phototrophic Synechococcus cyanobacteria dominated the NPP and CZ sites. Hydrographic parameters such as pH, salinity, biological oxygen demand, turbidity, and concentration of heavy metals (e.g., Cu and Fe) increased at the HV and CM sites compared with those at the NPP and CZ sites. This difference created more stressful conditions at the HV and CM sites. The microbial assemblages associated with T. aurea exhibited a prevalence of diverse symbiotic bacteria that could potentially contribute to the host’s ability to adapt and survive in challenging ecological conditions. Therefore, these advantageous microorganisms, along with the host’s physiological mechanisms of dispersion, range expansion, and invasiveness, may enhance the resilience and ability of T. aurea to thrive in extreme environments.

Volatile-char interactions during biomass pyrolysis: Effect of biomass acid-washing pretreatment - Yao Wang; Bin Li; Anjiang Gao; Kuan Ding; Xie Xing; Juntao Wei; Yong Huang; Jason Chun-Ho Lam; K.A. Subramanian; Shu Zhang (Fuel, 2023)

Relationship between meteorological variations, seasonal influenza, and hip fractures in the elderly: A modelling investigation using 22-year data - Conglu Li; Xiaoting Jiang; Qianying Yue; Yuchen Wei; Yawen Wang; Janice Ying-en Ho; Xiang Qian Lao; Ka Chun Chong (Science of The Total Environment, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Association between cold weather, influenza infection, and asthma exacerbation in adults in Hong Kong - Xi Xiong; Yuchen Wei; Holly Ching Yu Lam; Carlos King Ho Wong; Steven Yuk Fai Lau; Shi Zhao; Jinjun Ran; Conglu Li; Xiaoting Jiang; Qianying Yue; Wei Cheng; Huwen Wang; et al. (Science of The Total Environment, 2023)

Numerical Simulation of a Flat-Sheet Membrane-based Dehumidifier with Various Serpentine Flow Channels - Chun-Han Li; Hsuan-Yu Ho; Tien-Fu Yang; Mohammad Amani; Wei-Mon Yan (International Journal of Refrigeration, 2023)

Cassane diterpenoids from Caesalpinia pulcherrima and their anti-inflammatory and α -glycosidase inhibitory activities - Xin Yun; Xiu-Mei Chen; Jia-Yun Wang; Wang Lu; Zi-Han Zhang; Young Ho Kim; Shi-Chun Zong; Chun-Huan Li; Jin-Ming Gao (Natural Product Research, 2022)

Effect of Culture Period and Stocking Density on Input Demand and Scale Economies of Milkfish (Chanos chanos) Polycultures with White Shrimp (Penaeus indicus) - Wei-Tse Pai; Christian Schafferer; Jie-Min Lee; Li-Ming Ho; Yung-Hsiang Lu; Han-Chung Yang; Chun-Yuan Yeh (Fishes, 2022)
Milkfish, Chanos chanos, is one of the major inland cultured fish species in Taiwan. Variations in land resources and climate have led to the application of two distinct culture practices of milkfish polycultures with white shrimp, Penaeus indicus. This study applies a translog cost function model to analyze the production scale economy and input demand price elasticity of four milkfish polyculture systems with two different culture periods (OWC and NOWC) and two different white shrimp–milkfish fry stocking ratios (low SMR: 10–55 fry/ha; high SMR: 56–100 fry/ha). The findings show that the four milkfish polyculture systems require different operational adjustments to increase production while reducing the average culture cost. More specifically, overwinter cultures (OWC) have economies of scale. Farmers may reduce the average cost by expanding the production scale. Non-overwinter polycultures (NOWC) with high SMR are at the stage of decreasing return to scale, meaning that gains in output of milkfish cannot reduce the average cost. In terms of input factor use, farmers of OWC systems with high SMR are sensitive to fluctuations in the fry price since fry constitutes the input factor exhibiting the highest own-price elasticity. Moreover, fry and feed of OWC households with high SMR have high levels of substitutability, whereas fry and other input exhibit substitutability in OWC systems with low SMR. In NOWC farming households with high SMR, fry and capital have substitutability. It is thus recommended to modify the input factor use according to the culture mode and the white shrimp–milkfish stocking density ratio. Moreover, the study found that NOWCs have considerably higher SMR than OWCs, which may lead to a deterioration of the water quality in NOWC fishponds and lower survival rates. It is thus recommended to reduce the SMR to 31:1 to achieve economies of scale in production and increase the survival rate of milkfish and white shrimp.

Mechanical Properties and Energy Dissipation Characteristics of Coal–Rock-Like Composite Materials Subjected to Different Rock–Coal Strength Ratios - Yongchen He; Pengxiang Zhao; Shugang Li; Chun-Hsing Ho; Sitao Zhu; Xiangguo Kong; Diego Maria Barbieri (Natural Resources Research, 2021)

Inclination effect of coal mine strata on the stability of loess land slope under the condition of underground mining - Xue-yang Sun; Chun-Hsing Ho; Cheng Li; Yucheng Xia; Qi Zhang (Natural Hazards, 2020)

Efficacy of a Smartphone Hearing Aid Simulator - Cheng-Yu Ho; Pei-Chun Li; Shuenn-Tsong Young; Ying-Hui Lai (Journal of Medical and Biological Engineering, 2020)

Research on the effect of coal seam inclination on gas migration channels at fully mechanized coal mining face - Pengxiang Zhao; Risheng Zhuo; Shugang Li; Chun-Hsing Ho; Haifei Lin; Hui Liu (Arabian Journal of Geosciences, 2019)

Identification of sugar response complex in the metallothionein OsMT2b gene promoter for enhancement of foreign protein production in transgenic rice - Chia-Yu Chang; Kuo-Wei Lee; Chung-Shen Wu; Yu-Hsing Huang; Ho-Chun Chang; Chien-Lung Chen; Chen-Tung Li; Min-Jeng Li; Chung-Fu Chang; Peng-Wen Chen (Plant Cell Reports, 2019)

Enhancement of simultaneous batik wastewater treatment and electricity generation in photocatalytic fuel cell - Wan Fadhilah Khalik; Li-Ngee Ho; Soon-An Ong; Chun-Hong Voon; Yee-Shian Wong; Sara Yasina Yusuf; Nik Athirah Yusoff; Sin-Li Lee (Environmental Science and Pollution Research, 2018)

Characteristics of polycyclic aromatic hydrocarbons in PM2.5 emitted from different cooking activities in China - Yun-Chun Li; Jia-Qian Qiu; Man Shu; Steven Sai Hang Ho; Jun-Ji Cao; Ge-Hui Wang; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2018)

Ursolic acid activates the TGR5 receptor to enhance GLP-1 secretion in type 1-like diabetic rats - Shih-Hsiang Lo; Yingxiao Li; Kai Chun Cheng; Chiang-Shan Niu; Juei-Tang Cheng; Ho-Shan Niu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Expression of Iron Transporters and Pathological Hallmarks of Parkinson’s and Alzheimer’s Diseases in the Brain of Young, Adult, and Aged Rats - Li-Na Lu; Zhong-Ming Qian; Ka-Chun Wu; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2017)

Comparative Study of Photocatalytic Fuel Cell for Degradation of Methylene Blue under Sunlight and Ultra-Violet Light Irradiation - Sin-Li Lee; Li-Ngee Ho; Soon-An Ong; Guat-Mei Lee; Yee-Shian Wong; Chun-Hong Voon; Wan Fadhilah Khalik; Nik Athirah Yusoff; Noradiba Nordin (Water, Air, & Soil Pollution, 2016)

Preliminary Measurements of Binaural Masking-Level Difference When Using Hearing Aids for Sensorineural Hearing Loss - Cheng-Yu Ho; Pei-Chun Li; Shuenn-Tsong Young; Wen-Ying Yeh; Chih-Hung Wang; Woei-Chyn Chu (Journal of Medical and Biological Engineering, 2016)

Spatial short-term memory is impaired in dependent betel quid chewers - Meng-Chun Chiu; Bin Shen; Shuo-Heng Li; Ming-Chou Ho (Psychopharmacology, 2016)

Egr-1 deficiency protects from renal inflammation and fibrosis - Li-Chun Ho; Junne-Ming Sung; Yi-Ting Shen; Huei-Fen Jheng; Shun-Hua Chen; Pei-Jane Tsai; Yau-Sheng Tsai (Journal of Molecular Medicine, 2016)

Influence of supporting electrolyte in electricity generation and degradation of organic pollutants in photocatalytic fuel cell - Wan Fadhilah Khalik; Soon-An Ong; Li-Ngee Ho; Yee-Shian Wong; Chun-Hong Voon; Sara Yasina Yusuf; Nik Athirah Yusoff; Sin-Li Lee (Environmental Science and Pollution Research, 2016)

Chemical characteristics of rainwater in Sichuan basin, a case study of Ya’an - Yun-Chun Li; Meng Zhang; Man Shu; Steven Sai Hang Ho; Zi-Fang Liu; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2016)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

Anti-apoptotic protein BRE/BRCC45 attenuates apoptosis through maintaining the expression of caspase inhibitor XIAP in mouse Lewis lung carcinoma D122 cells - Yiu-Loon Chui; Chun-Hung Ma; Wei Li; Zhenyu Xu; Yao Yao; Frances Ka-Yin Lin; John Yeuk-Hon Chan; Kenneth Ka-Ho Lee (Apoptosis, 2014)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Sugar starvation- and GA-inducible calcium-dependent protein kinase 1 feedback regulates GA biosynthesis and activates a 14-3-3 protein to confer drought tolerance in rice seedlings - Shin-Lon Ho; Li-Fen Huang; Chung-An Lu; Siou-Luan He; Chun-Chin Wang; Sheng-Ping Yu; Jychian Chen; Su-May Yu (Plant Molecular Biology, 2013)

Differential neuronal changes in medial prefrontal cortex, basolateral amygdala and nucleus accumbens after postweaning social isolation - Yu-Chun Wang; Ue-Cheung Ho; Meng-Ching Ko; Chun-Chieh Liao; Li-Jen Lee (Brain Structure and Function, 2012)

Large-Eddy Simulation of Flow and Pollutant Transport in Urban Street Canyons with Ground Heating - Xian-Xiang Li; Rex E. Britter; Tieh Yong Koh; Leslie K. Norford; Chun-Ho Liu; Dara Entekhabi; Dennis Y. C. Leung (Boundary-Layer Meteorology, 2010)

Large-Eddy Simulation of Flow and Pollutant Dispersion in High-Aspect-Ratio Urban Street Canyons with Wall Model - Xian-Xiang Li; Chun-Ho Liu; Dennis Y. C. Leung (Boundary-Layer Meteorology, 2008)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)